KAJIAN ASAS SEDERHANA, CEPAT, DAN BIAYA RINGAN DALAM PROSES BERACARA PERDATA DI INDONESIA : STUDY OF THE PRINCIPLES OF SIMPLICITY, SPEED AND LOW COST IN CIVIL LITIGATION PROCESSES IN INDONESIA - Lubis, Fauziah; Putri, Nabilah Eka; Adelina, Adelina; Khairani, Mutia; Habeahan, Sinar Hidayat; Sari, Uci Pinkan (Gapenas Publisher, 2025)
This paper aims to examine the extent to which the application of the principle of simple, fast, and low cost in the civil procedure process in Indonesia is effective in facilitating public access to justice. Against the background of the need for an efficient and affordable procedural process, considering that there are still obstacles such as excessive formalities and lack of cooperation from litigants that hinder the implementation of these principles. Normative methods are used to analyze court regulations and practices to identify challenges and offer innovative solutions, such as simplifying procedures and utilizing information technology. This study found that although this principle has been regulated in Law No. 48 of 2009, consistent and comprehensive implementation is needed so that the justice system becomes inclusive and responsive to the needs of the community. This principle requires the efficient resolution of cases without neglecting the thoroughness of seeking truth and justice. Measures such as the merging of related cases and simpler summons mechanisms can increase the effectiveness of this principle. Therefore, this article provides important recommendations for interested parties to improve access and quality of justice in Indonesia through the optimal application of simple, fast, and low-cost principles.